2007
DOI: 10.1590/s0103-50532007000400006
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and lead retention in fresh and rotten red meat

Abstract: No presente trabalho foram avaliados os processos sortivos dos íons Cd 2+ e Pb 2+ em carne bovina em pH 6. Uma válvula de seleção de 8 canais foi utilizada para a mecanização do preparo das amostras e as concentrações de cádmio e chumbo foram determinadas por ICP-OES. Observou-se alta retenção (> 80%, m/m) dos íons Cd 2+ e Pb 2+ em carne fresca ou putrefata, indicando os riscos associados ao consumo de carne inadequadamente abatida, manipulada, estocada e/ou comercializada. Ácido acético a 1% (v/v) disponibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Meat consumption is considered a relevant source of Cd exposure based on the sorption and retention of Cd 2+ by amine groups in meat proteins (Lopes et al, 2007). Indeed, a previous study performed in Tenerife Island (Spain), González-Weller et al (2006) identified meat as a relevant exposure source.…”
Section: Predictors Of Adipose Tissue CD Concentrationsmentioning
confidence: 99%
“…Meat consumption is considered a relevant source of Cd exposure based on the sorption and retention of Cd 2+ by amine groups in meat proteins (Lopes et al, 2007). Indeed, a previous study performed in Tenerife Island (Spain), González-Weller et al (2006) identified meat as a relevant exposure source.…”
Section: Predictors Of Adipose Tissue CD Concentrationsmentioning
confidence: 99%
“…The high level of lead observed in the chicken muscle is supported by the work developed by Lopes et al 32 The authors noted high masses of lead and cadmium retained in both fresh and rotten bovine muscle and they warned about potential risks associated to the consumption of meat contaminated by Cd 2+ and Pb 2+ ions. The authors also associated the greatest retention of lead and cadmium ions in muscle tissue to the presence of chemical groupings in the proteins, which presented affinity with those metallic ions, such as sulfhydryl, carbonyl, hydroxyl and amine.…”
Section: Toxic Elements Contaminationmentioning
confidence: 79%
“…The way meats of different types are prepared [ 15 ], and especially storage conditions and handling, are potential sources of contamination and can significantly alter the levels of metals present in food [ 16 ], by placing food in contact with the contaminants. During the thermal processing of food, reactions that change color and taste occur, including the ones that result in toxic and mutagenic substances, such as furan, acrylamide, and acrolein [ 17 ].…”
Section: Introductionmentioning
confidence: 99%